(3TQM OjhGf GdfGHZI GdPHjGfi (B((3QhGjI GdCUeYj(B)s - (3CHh HcQ YGUe Hf CjhH GdHWdjehSis; (3RjGO Hf eYGhjI Hf VHGH GdPHjGfqj GdZWaGfqj GdeVQj, CHh CeGeI (B((3GdnqfGHnZI GdoqPrHnjGfj(B)s ((3eMeO Hf YHO GdYRjR (B( (3GHf GdHSGeI(B) s)
(3ChdgG (B:s
(3bGd GdfGHZI jeOM GdfYeGf Hf GdefPQ hjYJPQ Edjg(B: (3jG OGQ ejI HGdYdjGA aGdSfO CbhJ hWGd YdjgG SGda GdCHO s
(3BNQgG (B:s
(3hUa ai GdHjJ Cf GdYQH hGdYLe hGdJQc cGfhG jCedhfg hjQLhf NjQg ced TYQ GdfGHZI, QhGjI GdCUeYj,hTQM GHh HcQ YGUe Hf GjhH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdNW eged GdfbWs
(3GdfGHZI GdPHjGfi gh CHh CeGeI RjGO Hf eYGhjI Hf VHGH GdPHjGfi GdeJhai fMh (B18 (3b g`s
(3GdfSNI HgG MhGT s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs